Pengaruh Penerapan Microsoft Copilot terhadap Kinerja ASN di Lingkungan Rektorat Universitas Sriwijaya - Eka Sumantri; Anggun Rosalinda; Aulia Dayu Mu’arrifa (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
Microsoft Copilot is a generative AI technology that can help users compose, edit, and analyze documents automatically. By the end of 2024, the use of Copilot in Indonesia has grown rapidly, including in educational institutions and the government sector. However, the use of this technology by civil servants in higher education, particularly in the administrative realm of the rectorate, has rarely been studied in depth. The rectorate environment at Sriwijaya University has a high administrative workload and demands precision, so technology such as Copilot has great potential to improve the efficiency and quality of ASN work. This study aims to determine the extent to which the implementation of Microsoft Copilot affects the performance of ASN in the rectorate environment of Sriwijaya University. In addition, this study also analyzes the role of digital literacy and organizational support as factors that can strengthen the effectiveness of Copilot use in daily work. The research method uses a quantitative approach with a correlational design. Data was collected through questionnaires distributed to civil servants, then analyzed using regression to test the relationship between the variables of technology implementation and employee performance. The results of this study are expected to contribute to the development of a more adaptive campus bureaucracy digitalization strategy based on artificial intelligence technology.